2003
DOI: 10.1093/humrep/deg365
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte maturation, follicle rupture and luteinization in human cryopreserved ovarian tissue following xenografting

Abstract: Follicles cryopreserved within human ovarian tissue using the PROH procedure, can develop to the antral stage and undergo periovulatory changes following xenografting and exposure to a luteinizing stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 52 publications
1
47
2
2
Order By: Relevance
“…Likewise, only few human antral follicles developed from primordial follicles after xeno-transplantation into immune-deficient mice (32). One case of successful ovarian transplantation between monozygotic twins discordant for premature ovarian failure has been reported, and the patient delivered a healthy baby (33).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, only few human antral follicles developed from primordial follicles after xeno-transplantation into immune-deficient mice (32). One case of successful ovarian transplantation between monozygotic twins discordant for premature ovarian failure has been reported, and the patient delivered a healthy baby (33).…”
Section: Discussionmentioning
confidence: 99%
“…Snow et al (2002) demonstrated that oocytes that grow within mouse ovarian tissue xenografted to nude rats acquire the ability to generate pups. Ovarian tissues have been prepared from species phylogenetically distant from mice, including humans (Oktay et al 1998, Weissman et al 1999, Kim et al 2002, Gook et al 2003, dogs (Metcalfe et al 2001), monkeys (Candy et al 1995), sheep (Gosden et al 1994), cows (Senbon et al 2003), pigs (Kaneko et al 2003, Kagawa et al 2005, tammar wallaby (Mattiske et al 2002) and common wombats (Cleary et al 2003(Cleary et al , 2004, and xenografted to immunodeficient mice. To our knowledge, only one study (Kaneko et al 2003), in which neonatal pig ovarian tissues were xenografted, has proven that primordial oocytes can develop in the host mice and acquire fertilizing ability in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Cleary et al (2003) indicated that greater numbers of morphologically normal oocytes were recovered from ovarian grafts of common wombats after the host mice were given follicle-stimulating hormone (FSH) for 4 or 7 days. Treatment of host mice with FSH for over 20 weeks (Gook et al 2003), equine chorionic gonadotrophin (eCG) for 4 weeks (Kim et al 2002) or human menopausal gonadotrophin (hMG) for 14 days (Weissman et al 1999) increased the number of antral follicles within human ovarian xenografts, and the former two studies showed that some antral follicles formed early corpora lutea in response to human chorionic gonadotrophin (hCG; Kim et al 2002, Gook et al 2003 with resumption of meiosis of the oocytes (Gook et al 2003). We previously optimized the timing of eCG treatment of host mice in terms of follicular growth and oocyte recovery, and found that more oocytes with fertilizing ability were collected from antral follicles when eCG was given 60 days after estrus was first detected in the host mice (Kaneko et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Harvesting of ovarian tissue via laparoscopic surgery can be performed at any time during the menstrual cycle. Furthermore, the removal and appropriate cryopreservation of a small area of ovary containing an abundance of primordial follicles has more theoretical potential for future fertility than cryopreserved oocytes (Gook et al, 1999(Gook et al, , 2003. This tissue can then be reimplanted either orthotopically (Radford et al,2001;Meirow et al, 2005), or heterotopically (Donnez et al, 2004;Oktay et al, 2004;Wolner-Hanssen et al, 2005), with the demonstrated capacity to restore both endocrine function and fertility (Donnez et al, 2004;Meirow et al, 2005).…”
mentioning
confidence: 99%